KONSEP PENDIDIKAN ISLAM IBNU KHALDUN RELEVANSINYA TERHADAP PENDIDIKAN NASIONAL - Hidayat, Syamsul; Wakhidah, Ana Nur (Profetika, 2015)
Ibn Khaldun with all efforts to find a concept of Islamic education with some of them about the idea of learning known as malakah theory, generalization, tadarruj, and continuity, which until now is still used as a guide in the world of education. For this research trying to uncover the relationship between Islam Ibn Khalduns Concept of Education in Relevance of National Education. This study aims to provide an overview of the reasons behind Ibn Khalduns ideas with regard to the concept of Islamic education and describes the relevance of the concept of Islamic education Ibn Khaldun to the National Education. This research is a library research by using the method of collecting data is documentation research method, the research model by searching the data using the record of events that have passed such monumental works of Ibn Khaldun. From the analysis that has been done can be concluded that there is relevance of Ibn Khalduns concept of Islamic education to national education is characterized among other things by the similarity of the concept that the main object of education is a human being, in which man is composed of several basic elements are interrelated and can not be separated from each other.